Characterization of Cereal Cyst Nematode (Heterodera avenae) infecting wheat in Punjab - Kaur, Daman Jeet; Singh, Jaspreet (Journal of Cereal Research, 2025)
Three populations of Heterodera avenae collected from Wheat – Maize, Wheat – Cotton and Wheat – Rice rotation fields were characterized using two sets of Host differentials i.e., CCNHD 1982 and CCNHD Modified recieved from CIMMYT, Maxico. Reaction of all the host differentials was mostly the same to all three populations. Host differentials Ansi, Ortalan, Morocco and Bajo Aragon (CCNHD 1982) and VP1620 (CCNHD Modified) were resistant. The cultivars; Capa, Zita, Silva KVL 191, Siri, 1.376; CC4658, Iskamish K-2-Light, Martin 403-2, MK H. 72-646, Psathias and AUS 10894 from CCNHD 1982, while Raj 1, Croc_1/Ae.Squarrosa(224)// Opata//020615 and F372 from CCNHD Modified were moderately resistant to all three populations. Rest of the host differentials were categorized into moderately resistant to highly susceptible to one or other population. On the basis of the results obtained and compared with results of Andersen and Andersen (1982), Rivoal and Cook (1993) and Subbotin et al (2010), it was concluded that all the three populations belonged to same pathotype i.e., Ha 41 pathotype of Ha1 group.